Electrooptic proprieties of layer-by-layer films of a azobenzene containing copolymer - Ribeiro, Paulo A.; Gomes, Paulo J.; Ferreira, Quirina; Raposo, Maria; Dos Santos, David S.; Balogh, Débora T.; Oliveira Jr., Osvaldo N.; Giacometti, J. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
The methacrylic copolymer functionalized with the azo chromophore 4-[N-ethyl-N-(2-hydroxiethyl)]-amino-2′-chloro-4-nitroazobenzene (MMADR13), in its polyelectrolyte form, can be used to fabricate thin films by the layer-by-layer (LbL) technique just if one alternates this anionic polyelectrolyte with a cationic polyelectrolyte such as poly(allylamine hydrochloride) (PAH). Since PAH does not present any particular optical functionality, the main final film feature will came from the side chain DR13 azo-chromophore group due to its large nonlinear optical properties and photoisomerization capabilities. This work reports the electrooptic activity of MMADR13/DR13 LBL films, which arises from the high hiperpolarizability about the azo side chain group.
Keywords: Acrylic monomers; Azobenzene; Cationic polymerization; Chromophores; Copolymerization; Electrooptical effects; Anionic polyelectrolytes; Electrooptic proprieties; Layer by layer films (LbL); Methacrylic copolymer; Polymer films